PERSEPSI PETANI TERHADAP PERAN PENYULUH DI DESA DUREN, KABUPATEN SEMARANG PROVINSI JAWA TENGAH INDONESIA - Rizka Muflikhatun Nisa’; Tinjung Mary Prihtanti (Agros Journal of Agriculture Science, 2024)
Duren Village, Tengaran District, Semarang Regency, Central Java Province, Indonesia, is one of the central villages for rice farming development. Agricultural extension and farmer group leadership also play a role in optimizing the function of farmer groups in Duren Village. This research aims to determine farmers' perceptions of the role of agricultural instructors in Duren Village, including their roles as motivators, educators, dynamists, facilitators, and innovators. The type of research is quantitative descriptive with a total of 84 rice farmers as respondents determined using proportional random sampling. The research results show that the role of agricultural instructors in Duren Village, Tengaran District, Semarang Regency as motivators, educators, dynamists, facilitators, and innovators is in the high category. This shows that the role of extension workers is crucial in increasing community knowledge, skills, and awareness. Extension workers contribute significantly to encouraging positive change, empowering groups, and facilitating the implementation of innovations and technologies that support sustainable agriculture.